Identification of Waste Processing Methods in Bersinar Waste Bank Bandung, West Java - Nurul Mawaddah; Febrian Rahmat Adias Putra (Indonesian Journal of Environmental Management and Sustainability, 2022)
The bersinar waste bank is one of the waste management units in Bandung. The bersinar waste bank is a solution to reduce waste generation at the sarimukti TPA, Bandung. Waste managed by the bersinar waste bank is in the form of organic and inorganic waste. This study aims to identify the methods of processing waste and processing products at the bersinar waste bank in Bandung. This research is a qualitative research. The stages of this research are problem identication, literature review, determination of research aims and objectives, data collection, data analysis and interpretation, and reporting. This research data collection is divided into two, namely primary data (observation) and secondary data obtained from books or scientic journals (literature review). The results of the identication of waste processing methods at the bersinar waste bank can be concluded that the bersinar waste bank uses physical, biological and thermal methods. The rst method to reduce waste is to process organic waste using maggot technology as a decomposer of organic waste into compost. the second method is the use of a bottle press to produce a cube of bottle waste. The third method is processing used baby diaper waste using a hydrothermal reactor machine and processing it into ber to produce pockbrick.